ANALISIS KESADARAN MASYARAKAT DI KOTA BANDUNG TERHADAP TERJADINYA PENCEMARAN LINGKUNGAN - Ageng Saepudin Kanda; Neng Santy (CV. ALIM'SPUBLISHING, 2024)
Abstraks: The city of Bandung faces big challenges in waste management, with daily waste production of 3,950 tons and only 2,750 tons being transported. High population density and intense tourism contribute to waste production, which causes rubbish to be scattered in cities and rivers. Therefore, this research was carried out with the aim of analyzing what causes environmental pollution in the city of Bandung to continue to increase. This research was carried out using a descriptive qualitative method, namely by taking a sample of respondents from the city of Bandung to analyze what factors cause people's lack of concern for the environment. According to the results obtained, it is the lack of awareness of the people of Bandung city which is a factor causing the high level of environmental pollution, in addition to the lack of knowledge on how to process waste properly so that the waste does not accumulate and everything can be recycled. The program carried out by the government also educates the local community on how to process waste using the 4R method and also sorting waste before disposal and by cultivating waste that can be recycled. Keywords: Garbage, environment, pollution, society, cleanliness.